High-thermal-conductivity graphene-boron nitride composite epoxy resin material and preparation method thereof
By adding magnetized graphene-boron nitride filler to the polymer material and using the external magnetic field to make its contact more sufficient, the problem of low thermal conductivity of the polymer material is solved, and a composite material with high thermal conductivity is achieved, and the friction coefficient is reduced.
Patent Information
- Application Number
- CN202510034213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The intrinsic thermal conductivity of existing polymer materials is low, making it difficult to effectively improve thermal conductivity, and the filler content is too low that it cannot effectively improve the thermal conductivity. At the same time, the filler is prone to agglomeration, which makes it difficult to form thermal conductivity channels.
By adding the magnetized graphene-boron nitride filler to the epoxy resin, and using the external magnetic field to make the filler contact more fully and arrange in an orderly manner, thereby improving the thermal conductivity of the composite material.
The thermal conductivity of the composite material has been increased to 2.1 (W/mk), and the friction coefficient is effectively reduced, which is reduced by about 30% compared with pure epoxy resin.
Smart Images

Figure CN119823531A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive materials, and specifically relates to a graphene-boron nitride composite epoxy resin material and a preparation method thereof. Background Art
[0002] As all kinds of electronic components become increasingly miniaturized and highly integrated, they will inevitably face a problem. Heat tends to accumulate quickly in a short period of time, and high heat often affects the stable operation and service life of instrument components. Therefore, further improving the heat dissipation capacity of the thermal management system has become one of the urgent problems to be solved.
[0003] Although a heat sink can carry away some of the heat through the flow of air, sometimes the heat source cannot be directly exposed to the outside world. Therefore, the internal heat needs to be conducted away using materials with good thermal conductivity. There are many materials with high intrinsic thermal conductivity, including metal materials such as silver and copper. However, the disadvantages of metals, such as high thermal conductivity, high electrical conductivity, easy corrosion, high cost and plasticity, limit their application scope in thermal management applications.
[0004] Compared with metals, polymers have many advantages. They are not only low in cost but also have excellent corrosion resistance, electrical insulation and good processability. Polymers can be used as coating materials applied to metal devices as a protective layer. They can be used as packaging materials for electronic components or phase change materials. For example, epoxy resins can often be used for chip packaging and potting and sealing of motors. As an adhesive, it can effectively bond metals and can also be used as an electrical insulating substrate material for copper-clad laminates. In addition, epoxy resins can also be used in railway transportation systems and sliding contact materials for electric motors. However, since most polymers are composed of long-chain molecules, when the curing reaction occurs, the molecular chains randomly cross-link with each other. This causes the long polymer chains to be in a disordered state, so the intrinsic thermal conductivity of the polymer is often very low (less than 0.2w / mk 13 ). At the same time, given that improving the intrinsic thermal conductivity of polymers is costly and difficult, and the degree of improvement is not high. Therefore, a simple and effective way to improve the thermal conductivity of polymer materials is to fill the polymer with thermal conductive fillers. For example, adding metal powder or inorganic non-metallic materials such as aluminum oxide, boron nitride, graphene, carbon fiber, silicon carbide, etc. The thermal conductive network formed by the filler in the polymer is used to improve the overall thermal conductivity of the polymer. The shape and dispersion of the filler, and the interfacial thermal resistance caused by the mismatch of energy carriers between different materials will affect the formation of the thermal conductive network and the transmission performance of phonons in the thermal conductive network. At the same time, there is usually a threshold for the filler content when forming a thermal conductive channel, even if a single layer of graphene has an ultra-high anisotropic intrinsic thermal conductivity of 5300w / mk 13However, if the content is too low, it cannot effectively improve the thermal conductivity of the resin. In addition, its large specific surface area causes the graphene filler to easily agglomerate in the resin, making it difficult to form a thermal conductive channel and more serious phonon scattering. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, an object of the present invention is to overcome the deficiencies in the prior art and provide a graphene-boron nitride composite epoxy resin material with high thermal conductivity.
[0008] The graphene-boron nitride composite epoxy resin material is obtained from magnetized graphene-boron nitride modified epoxy resin;
[0009] The saturation magnetization intensity of the magnetized graphene-boron nitride is 15 to 20 emu / g, and the thermal conductivity of the modified epoxy resin material is greater than 2 w / mk.
[0010] As a preferred solution of the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the amount of the magnetized graphene-boron nitride compared to the total mass of the epoxy resin and its curing agent is 5% to 25%.
[0011] As a preferred solution of the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the friction coefficient of the composite epoxy resin material is reduced by 32% to 40% compared with the unmodified epoxy resin.
[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a graphene-boron nitride composite epoxy resin material with high thermal conductivity.
[0013] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0014] Graphene-boron nitride is added to a mixed solution of pure water and anhydrous ethanol, a mixed solution containing ferrous sulfate and ferric chloride is added thereto, and the mixture is sealed and stirred to obtain a mixed solution I;
[0015] The pH of the mixed solution I is adjusted to be alkaline, and the mixture is heated to react until the solid is completely precipitated, and then filtered, washed, and dried to obtain a magnetized graphene-boron nitride filler;
[0016] The epoxy resin and the curing agent are stirred until fully mixed to obtain a mixture I, to which a magnetized graphene-boron nitride filler of 5% to 25% by mass of the mixture I is added, and after stirring, the mixture is vacuum degassed and poured into a silicone mold for room temperature curing to obtain a magnetized graphene-boron nitride epoxy resin.
[0017] As a preferred embodiment of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the method for preparing the graphene-boron nitride comprises:
[0018] Graphene and boron nitride are mixed in a ratio of 3-4:6-7 and added into a mixed solution of anhydrous ethanol and water, and PSS with a mass fraction of 15-20% is added thereto after ultrasonic treatment, and graphene-boron nitride is obtained through stirring, filtering and washing.
[0019] As a preferred solution of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the content of ferrous sulfate and ferric chloride in the mixed solution I is 22-30% of the graphene boron nitride.
[0020] As a preferred embodiment of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, wherein: the mass ratio of ferrous sulfate to ferric chloride in the mixed solution I is 3 to 5:2
[0021] As a preferred embodiment of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the pH of the mixed solution I is adjusted to 11-12.
[0022] As a preferred embodiment of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the pH of the mixed solution I is adjusted to 11-12.
[0023] As a preferred solution of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the reaction temperature of the heating reaction is 30-60°C.
[0024] As a preferred solution of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, the vacuum degassing time is 30 to 50 minutes.
[0025] As a preferred solution of the method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material of the present invention, wherein: the curing time of the room temperature curing is 32 to 40 hours.
[0026] Beneficial effects of the present invention:
[0027] The present invention modifies the surface of graphene-boron nitride filler to obtain a filler with magnetic response, adds the filler to epoxy resin, and uses the external magnetic field to make the filler contact more fully and arrange, thereby effectively improving the thermal conductivity of the composite material. Through testing, it was found that when the filler accounts for 25%, the thermal conductivity reaches 2.1 (W / mk), and it can effectively reduce the friction coefficient, which is about 30% lower than that of pure epoxy resin. This study provides a new idea and method for preparing epoxy resin-based composite materials with high thermal conductivity, and expands new fields and directions for the application of epoxy resin in the field of electronic packaging, which has practical significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is an elemental analysis diagram of the magnetized graphene-boron nitride ring filler prepared in Example 1 of the present invention.
[0030] Figure 2 XRD analysis diagram and hysteresis loop of the magnetized graphene-boron nitride ring filler prepared in Example 1 of the present invention.
[0031] Figure 3 This is a SEM image of the magnetized graphene-boron nitride epoxy resin prepared in Example 1 of the present invention.
[0032] Figure 4 This is a comparison chart of the surface hardness and friction coefficient results of the magnetized graphene-boron nitride epoxy resin and pure epoxy resin obtained under different filler loading amounts in Examples 2 to 6 of the present invention and Comparative Example 1.
[0033] Figure 5 The surface hardness and friction coefficient of the products of Examples 1 to 5 of the present invention and Comparative Example 1 are compared. Figure 6 The figure is a comparison of thermal conductivity between the products of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art, including:
[0038] Graphene (multilayer graphene has 3 to 4 layers) was purchased from Guangxi Qinglu New Materials Technology Co., Ltd.;
[0039] Boron nitride (sheet diameter 1 μm) was purchased from Shanghai Yaoge Alloy Materials Co., Ltd.;
[0040] Ferric chloride hexahydrate (analytical grade) was purchased from Shanghai Zhanyun Chemical Co., Ltd.;
[0041] Ferrous sulfate hexahydrate and sodium hydroxide were purchased from Sichuan Longxi Science Co., Ltd.;
[0042] Anhydrous ethanol was purchased from Chengdu Kelong Chemical Co., Ltd.;
[0043] Ultrapure water was produced by an ultrapure water machine (Hangzhou Yijie Technology Co., Ltd.);
[0044] Epoxy resin and curing agent (fatty amine curing agent) were purchased from Shanghai Aotun Chemical Technology;
[0045] Sodium poly(vinylbenzenesulfonate) (PSS) was purchased from Anhui Cool Bioengineering Co., Ltd.
[0046] The performance test of the obtained material in the present invention is carried out according to the following method:
[0047] Thermal conductivity: The thermal conductivity of epoxy resin composite materials with different filler ratios was tested using a DRP2-thermal conductivity tester. The measured samples were cylindrical samples with a diameter of 50 mm and a thickness of 3-5 mm.
[0048] Friction performance: The friction coefficient of the composite material was tested using a friction and wear tester UMT. A load of 10N was applied at room temperature, and the friction was cyclically rubbed at 5HZ for 30 minutes to obtain a curve of the friction coefficient changing with time;
[0049] The friction interface morphology was characterized using a white light interferometer to obtain the wear volume V during the friction process. The wear rate was calculated using the formula: Ws = v / w (where v represents the wear volume and W represents the work done by the friction force). Since the experimental conditions during the friction and wear test were 30 minutes of cyclic friction under an applied load of 10N and the steel ball traveled 30 mm within 1 second, it can be calculated that the distance the friction force did work was 54m. Multiple measurements were taken to obtain the average friction coefficient of each group of composite materials at different proportions, and then the average friction force during the friction process was obtained.
[0050] Surface hardness: Vickers hardness tester was used to measure the surface hardness of composite materials with different filler proportions.
[0051] Characterization of morphology: The prepared magnetized graphene-boron nitride filler was tested by the EDS function of the scanning electron microscope (SEM) to see whether the surface of the filler was adsorbed with iron oxide elements, and the distribution of the filler inside the epoxy resin composite material was observed by scanning electron microscopy. XRD was used to characterize the type of iron oxide on the surface of the filler, and VSM was used to measure the saturation magnetization intensity of the filler. Finally, a white light interferometer was used to characterize the morphology of the friction interface of the composite material and calculate the change in wear rate under different filler proportions.
[0052] Example 1
[0053] The present embodiment provides a magnetized graphene-boron nitride composite epoxy resin material, which is obtained by modifying epoxy resin with magnetized graphene-boron nitride, wherein the amount of magnetized graphene-boron nitride compared to the total mass of epoxy resin and curing agent is 5-25%, the saturation magnetization intensity of magnetized graphene-boron nitride is 16.4emu / g, its thermal conductivity is 0.53-2.1 (w / mk), and the friction coefficient is 0.406-0.512, which is reduced by 32-40% compared with unmodified epoxy resin. The corresponding properties of epoxy resin modified with different contents of magnetized graphene-boron nitride are shown in Table 1.
[0054] Table 1
[0055]
[0056]
[0057] Example 2
[0058] This embodiment provides a method for preparing a magnetized graphene-boron nitride composite epoxy resin material, specifically:
[0059] 1) 15 g of graphene and 35 g of boron nitride were added to a mixed solution of 300 ml of pure water and 300 ml of anhydrous ethanol, and ultrasonically treated for 60 min to obtain a mixed solution I;
[0060] Add 20 ml of 20% PSS to the mixed solution I, stir at 300 r / min for 180 min, filter, and wash the obtained product with anhydrous ethanol to obtain graphene-boron nitride;
[0061] 2) Graphene-boron nitride is added to a mixed solution of 300 ml of pure water and 300 ml of anhydrous ethanol, and then 400 ml of a mixed solution of ferrous sulfate and ferric chloride is added thereto, wherein ferrous sulfate is 6 g and ferric chloride is 5 g. At this time, the total amount of ferrous sulfate and ferric chloride is 22% of the graphene-boron nitride. After sealed and stirred for 90 minutes, the pH value of the solution is adjusted to 12 using sodium hydroxide, and reacted at 60° C. until the solid is completely precipitated, and then filtered, washed and dried using anhydrous ethanol to obtain a magnetized graphene-boron nitride filler (MG-BN).
[0062] Figure 1 is the elemental analysis diagram of the graphene-boron nitride filler prepared in this embodiment, Figure 1 As shown in the EDS elemental analysis diagram of cf, the elements contained in the filler include carbon, nitrogen, boron, iron and oxygen, indicating that ferric chloride and ferrous sulfate hexahydrate can generate iron oxide on the surface of graphene and boron nitride under alkaline conditions, thereby preparing a thermally conductive filler with magnetic response.
[0063] Figure 2 The XRD analysis diagram and hysteresis loop of the magnetized graphene-boron nitride filler prepared in this embodiment are as follows: Figure 2 As shown in a, the XRD test of the prepared MG-BN filler, where the starting angle is 5°, the ending angle is 90°, and the step speed is 0.2° per minute. The results show that the iron oxide contained in the MG-BN filler is Fe 3 O 4 , and according to Figure 2 b It can be seen that the saturation magnetization intensity of the filler is 16.4emu / g.
[0064] 3) Weighing epoxy resin and curing agent in a ratio of 3:1, mechanically stirring to fully mix them to obtain a mixture I, adding 25% of the mass of the magnetized graphene-boron nitride filler compared to the mixture I, stirring for 20 minutes and then placing it in a vacuum box for degassing for 40 minutes, then pouring it into a silicone mold, and placing the mold between two circular magnets, curing at room temperature for 36 hours, and obtaining the magnetized graphene-boron nitride epoxy resin.
[0065] like Figure 3 As shown, Figure 3 ac is the cross-sectional view of the graphene-boron nitride-epoxy resin composite material after curing under an external magnetic field. Figure 3df is a cross-sectional view of the epoxy resin composite material after curing without applying a magnetic field to the outside. The contact between fillers is a necessary condition for the formation of a heat conduction channel. The key to improving the thermal conductivity of the composite material is that the fillers are well dispersed and can maintain a large area of contact. When there is no magnetic field, although the fillers can be stacked and contacted with each other, the fillers are unevenly distributed and staggered. The reason for this situation may be that graphene-boron nitride is a flaky material, which is randomly arranged in epoxy resin, resulting in various contact forms between fillers, such as line-surface contact and surface-surface contact. This also makes it easier to generate gaps inside the filler, affecting the continuity of the heat conduction channel. Under the action of an external magnetic field, although the staggered distribution of fillers cannot be completely eliminated, a significant improvement can be observed. The reason is that the fillers in the epoxy resin will be arranged along the direction of the magnetic flux lines or deflected to a certain extent under the action of an external magnetic field. While improving the orientation of the fillers, the fillers are in closer contact, which is conducive to the transmission of phonons between fillers and reduces scattering.
[0066] Example 3
[0067] The difference between this embodiment and embodiment 2 is that the mass of the magnetized graphene-boron nitride filler added in step 3) is adjusted to 5% compared to the mass of mixture I, and the remaining steps and processes are all referred to embodiment 2 to obtain the magnetized graphene-boron nitride epoxy resin of this embodiment.
[0068] Example 4
[0069] The difference between this embodiment and embodiment 2 is that the mass of the magnetized graphene-boron nitride filler added in step 3) is adjusted to 10% compared to the mass of mixture I, and the remaining steps and processes are referred to embodiment 2 to obtain the magnetized graphene-boron nitride epoxy resin of this embodiment.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 2 is that the mass of the magnetized graphene-boron nitride filler added in step 3) is adjusted to 15% compared to the mass of mixture I, and the remaining steps and processes are all referred to embodiment 2 to obtain the magnetized graphene-boron nitride epoxy resin of this embodiment.
[0072] Example 6
[0073] The difference between this embodiment and embodiment 2 is that the mass of the magnetized graphene-boron nitride filler added in step 3) is adjusted to 20% compared to the mass of mixture I, and the remaining steps and processes are all referred to embodiment 2 to obtain the magnetized graphene-boron nitride epoxy resin of this embodiment.
[0074] Comparative Example 1
[0075] This comparative example uses pure epoxy resin as a comparison, that is, the filler content thereof is 0, which is denoted as P.
[0076] Figure 4 The surface hardness and friction coefficient results of magnetized graphene-boron nitride epoxy resin and pure epoxy resin were obtained under different filler loading amounts in Examples 2 to 6 and Comparative Example 1.
[0077] like Figure 4 As shown in a, with the increase of graphene-boron nitride filler content, the surface hardness of epoxy resin composite material increases slightly. This is because the hardness of the filler itself is higher than that of epoxy resin and when the epoxy resin composite material is subjected to the positive pressure of the hardness tester probe, the epoxy resin deforms. The thermal conductive filler can provide a fulcrum for the epoxy resin, making the composite material less deformed and the surface hardness increased. The tribological properties of epoxy resin are also affected by its hardness;
[0078] like Figure 4 As shown in b, the friction coefficient curve on epoxy resin UMT without filler shows that the friction coefficient of pure epoxy resin is about 0.67. As fillers are added, the average friction coefficient of the composite material gradually decreases from 0.67. When the filler ratio is 5%, 10%, 15%, 20%, and 25%, the average friction coefficient of the composite material is 0.512, 0.497, 0.452, 0.431, and 0.406, respectively. The reason may be that the introduced filler falls off during the friction process, which causes the graphene-boron nitride to form a transfer layer at the friction interface, reducing the heat accumulated during the friction process while effectively reducing the friction coefficient. Among them, the wear scar surface with a filler ratio of 15%, 20%, and 25% is relatively flat, and the friction coefficient is reduced by 32% to 40% compared with pure epoxy resin.
[0079] Figure 4 c-e show that the wear scar of the pure epoxy resin group is very rough, and the morphology of the wear scar shows that the extension direction of the wear scar is not exactly the same as the friction direction. This is because the macromolecules of the epoxy resin have a strong adhesion after curing, and the pure epoxy resin is brittle, so the material itself is torn off or large pieces of debris fall off during the friction process, forming more pits.
[0080] and Figure 4 The results of f show that the wear rate of the composite material increases with the increase of filler loading, that is, the addition of fillers will reduce the mechanical properties of the resin to a certain extent.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Examples 2 to 6 is that the magnetized graphene-boron nitride filler is replaced with boron nitride, specifically:
[0083] Epoxy resin and curing agent were weighed in a ratio of 3:1, and mechanical stirring was performed to fully mix them to obtain a mixture I, to which a boron nitride filler in an amount of 25% by mass compared to the mixture I was added, and after stirring for 20 minutes, the mixture was placed in a vacuum box for degassing for 40 minutes, and then poured into a silicone mold, and the mold was placed between two circular magnets, and cured at room temperature for 36 hours to obtain a boron nitride epoxy resin (BN).
[0084] Comparative Example 3
[0085] The difference between this comparative example and Examples 2 to 6 is that step 2) is omitted and the filler is not subjected to magnetization treatment. Specifically:
[0086] Epoxy resin and curing agent were weighed in a ratio of 3:1, and mechanical stirring was performed to fully mix them to obtain a mixture I, to which 25% of the mass of graphene-boron nitride filler compared to the mass of mixture I was added, and after stirring for 20 minutes, it was placed in a vacuum box for degassing for 40 minutes, and then poured into a silicone mold, and the mold was placed between two circular magnets, and cured at room temperature for 36 hours to obtain graphene-boron nitride epoxy resin (G-BN).
[0087] The thermal conductivity results of the magnetized graphene-boron nitride epoxy resin obtained under different filler loadings in Examples 2 to 6 and the epoxy resins in Comparative Examples 1 to 3 are as follows: Figure 5 As shown in the figure, when boron nitride, graphene-boron nitride and magnetically responsive graphene-boron nitride are used as thermal conductive fillers, the thermal conductivity of the composite materials increases with the increase of filler loading. The reason is that increasing the content makes it easier for the fillers to contact each other, thereby forming a thermal conductive channel in the polymer.
[0088] At the same time, under the same filler loading, the thermal conductivity of the graphene-boron nitride composite material without magnetic field orientation is higher than that of the boron nitride composite material. This shows that under the same filler mass, the introduction of graphene with high intrinsic thermal conductivity improves the overall thermal conductivity of the composite material.
[0089] When comparing the thermal conductivity between the orientation groups with and without magnetic field, the thermal conductivity of the composite material oriented by magnetic field is higher than that of the non-oriented composite material. This is because the external magnetic field orients the filler, making the contact between graphene-boron nitride fillers closer, and the order of the filler is higher than that of the randomly arranged filler, which is more conducive to heat conduction. When the mass proportion of thermal conductive filler is 25%, the thermal conductivity can reach 2.1 (w / mk), and the volume resistivity can reach 4.634×10 at 500V. 12Ω·cm. Experiments have found that when the mass proportion of fillers is further increased (such as 30%), the viscosity of the resin system is too high. When the viscosity is too high, it affects the magnetic field effect and the subsequent vacuum degassing. During curing, a large number of air bubbles are likely to appear, affecting the thermal conductivity and mechanical properties. Therefore, the mass proportion of thermal conductive fillers is preferably less than 25%.
[0090] Comparative Example 4
[0091] The difference between this comparative example and Example 2 is that the amount of ferrous sulfate in step 2) is adjusted to 2 g and the amount of ferrous chloride is 1 g. At this time, the total amount of ferrous sulfate and ferric chloride is 6% of the graphene-boron nitride. The remaining steps and processes are all based on Example 2 to obtain the magnetized graphene-boron nitride filler and magnetized graphene-boron nitride epoxy resin of this comparative example.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 2 is that the amount of ferrous sulfate in the adjustment step 2) is 2 g, and the amount of ferric chloride is 3 g. At this time, the total amount of ferrous sulfate and ferric chloride is 10% of the graphene-boron nitride. The remaining steps and processes are all based on Example 2 to obtain the magnetized graphene-boron nitride filler and magnetized graphene-boron nitride epoxy resin of this comparative example.
[0094] Comparative Example 6
[0095] The difference between this comparative example and Example 2 is that the amount of ferrous sulfate in the adjustment step 2) is 5 g, and the amount of ferric chloride is 3 g. At this time, the total amount of ferrous sulfate and ferric chloride is 16% of the graphene-boron nitride. The remaining steps and processes are all based on Example 2 to obtain the magnetized graphene-boron nitride filler and magnetized graphene-boron nitride epoxy resin of this comparative example.
[0096] Comparative Example 7
[0097] The difference between this comparative example and Example 2 is that the amount of ferrous sulfate in the adjustment step 2) is 10 g, and the amount of ferric chloride is 5 g. At this time, the total amount of ferrous sulfate and ferric chloride is 30% of the graphene-boron nitride. The remaining steps and processes are all based on Example 2 to obtain the magnetized graphene-boron nitride filler and magnetized graphene-boron nitride epoxy resin of this comparative example.
[0098] Comparative Example 8
[0099] The difference between this comparative example and Example 2 is that the amount of ferrous sulfate in the adjustment step 2) is 10g, and the amount of ferric chloride is 15g. At this time, the total amount of ferrous sulfate and ferric chloride is 50% of the graphene-boron nitride. The remaining steps and processes are all based on Example 2 to obtain the magnetized graphene-boron nitride filler and magnetized graphene-boron nitride epoxy resin of this comparative example.
[0100] The saturation magnetization intensity of the magnetized graphene-boron nitride filler obtained in Comparative Examples 4 to 8 and the thermal conductivity of the graphene-boron nitride epoxy resin obtained were measured and compared with those in Example 2. The results are as follows: Figure 6 And as shown in Table 2.
[0101] Table 2
[0102]
[0103] Figure 6 a~ Figure 6 e is the saturation magnetization of the filler when the content of the magnetic modification additive is 6%, 10%, 16%, 22% and 50%, respectively. It can be seen that with the increase of the content of the magnetic modification additive, the saturation magnetization of the filler also shows an upward trend, but the numerical thermal conductivity is not proportional to the saturation magnetization of the filler. When the saturation magnetization of the filler reaches a certain value, the thermal conductivity of the resin cannot be further improved, and may even decrease. When the magnetism of the filler is too strong, the dispersion of the filler in the resin matrix may deteriorate due to the magnetic field, forming agglomeration or local high concentration areas. Agglomerated fillers will not only reduce the thermal conductivity of the material, but also increase the interface thermal resistance, affecting the effective transfer of heat.
[0104] In addition, the filler can be oriented by applying an external magnetic field, thereby improving the thermal conductivity of the material. However, when the filler is too magnetic, the magnetic field orientation may become difficult or uncontrollable, resulting in a disorderly arrangement of the filler, which in turn reduces the thermal conductivity.
[0105] In summary, the present invention modifies the surface of graphene-boron nitride filler to obtain a filler with magnetic response, adds the filler to the epoxy resin, and uses the external magnetic field to make the filler contact more fully and arrange in an orderly manner, thereby effectively improving the thermal conductivity of the composite material. Through testing, it was found that when the filler accounts for 25%, the thermal conductivity reaches 2.1 (W / mk), and it can effectively reduce the friction coefficient, which is about 30% lower than that of pure epoxy resin. This study provides a new idea and method for the preparation of epoxy resin-based composite materials with high thermal conductivity, and expands new fields and directions for the application of epoxy resin in the field of electronic packaging, which has practical significance.
[0106] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A high thermal conductivity graphene-boron nitride composite epoxy resin material, characterized in that: The graphene-boron nitride composite epoxy resin material is obtained from magnetized graphene-boron nitride modified epoxy resin; The saturation magnetization intensity of the magnetized graphene-boron nitride is 15 to 20 emu / g, and the thermal conductivity of the modified epoxy resin material is greater than 2 w / mk.
2. The high thermal conductivity graphene-boron nitride composite epoxy resin material according to claim 1, characterized in that: The amount of the magnetized graphene-boron nitride used is 5% to 25% of the total mass of the epoxy resin and its curing agent.
3. The high thermal conductivity graphene-boron nitride composite epoxy resin material according to any one of claims 1 or 2, characterized in that: The friction coefficient of the composite epoxy resin material is reduced by 32% to 40% compared with that of unmodified epoxy resin.
4. A method for preparing a high thermal conductivity graphene-boron nitride composite epoxy resin material, characterized in that: include, Graphene-boron nitride is added to a mixed solution of pure water and anhydrous ethanol, a mixed solution containing ferrous sulfate and ferric chloride is added thereto, and the mixture is sealed and stirred to obtain a mixed solution I; The pH of the mixed solution I is adjusted to be alkaline, and the mixture is heated to react until the solid is completely precipitated, and then filtered, washed, and dried to obtain a magnetized graphene-boron nitride filler; The epoxy resin and the curing agent are stirred until fully mixed to obtain a mixture I, to which a magnetized graphene-boron nitride filler of 5% to 25% by mass of the mixture I is added, and after stirring, the mixture is vacuum degassed and poured into a silicone mold for room temperature curing to obtain a magnetized graphene-boron nitride epoxy resin.
5. The method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material according to claim 4, characterized in that: The preparation method of graphene-boron nitride comprises: Graphene and boron nitride are mixed in a ratio of 3-4:6-7 and added into a mixed solution of anhydrous ethanol and water, and PSS with a mass fraction of 15-20% is added thereto after ultrasonic treatment, and graphene-boron nitride is obtained through stirring, filtering and washing.
6. The method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material according to any one of claims 4 or 5, characterized in that: The content of ferrous sulfate and ferric chloride in the mixed solution I is 22-30% of the graphene boron nitride.
7. The method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material according to claim 6, characterized in that: The mass ratio of ferrous sulfate to ferric chloride in the mixed solution I is 3-5:
2.
8. The method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material according to any one of claims 4, 5 or 7, characterized in that: The pH of the mixed solution I is adjusted to 11-12.
9. The method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material according to claim 8, characterized in that: The reaction temperature of the heating reaction is 30-60°C.
10. The method for preparing the high thermal conductivity graphene-boron nitride composite epoxy resin material according to claim 1, characterized in that: The vacuum degassing time is 30 to 50 minutes.
Citation Information
Patent Citations
High-directional-thermal-conductivity carbon / polymer composite material and preparation method
CN105001450A
Boron nitride insulating and heat-conducting material, preparation method and application
CN117024914A
Carbon fiber reinforced resin composite material as well as preparation method and application thereof
CN118791845A
Cited By
Heat-conducting interface material as well as preparation method and application thereof
CN120484449A
A thermally conductive interface material and its preparation method and application
CN120484449B
Hot glue for composite material and preparation method thereof
CN121950247A